Analisis Respon Time Command Car Dalam Operasi PKP-PK di Bandar Udara Supadio Pontianak Kalimanatan Barat - Wirsa Maulana (Jurnal Indonesia Sosial Sains, 2022)
The sorts of air transportation modes on the planet are progressively sought after by numerous travelers. The more individuals who do transportation, the higher the gamble of peril caused, so the Public authority is considered extremely significant to cause guidelines that to control the freedoms and commitments of each and every entertainer in the aeronautics world and for the security of flight itself. One of the endeavors to guarantee the security of the public authority's flights, aside from laying out an establishment whose errand is to direct the smooth running of flights, is likewise to frame a foundation called the Aeronautics Mishap Alleviation Administration and Putting out fires Administration (PKP-PK). The reason for the exploration of this pkp-pk unit itself is a direct result of the incessant event of postponements in the PKP-PK unit, particularly on order vehicles where for the practicality of an order vehicle it ought to require 3 minutes to show up at the scene at the most recent. The strategy utilized in this examination is the technique for direct perception and field perception. Toward the finish of the section, it has been made sense of the motivation behind why the order vehicle unit can be late, which is brought about by one of the principal factors being some unacceptable area of the pkp-pk unit post and the shortfall of a unique way for the activity of the order vehicle.